Estudo sobre os fatores que influenciaram a evasão no curso de administração da UFMA, na modalidade a distância, no pólo presencial de Porto Franco MA - ZORDAN, Giselli Ramos (2012)
The impressive growth of higher education in Brazil is the distance at the same time, a contrast to the vacancies offered and a high dropout rate. Although avoidance is not a privilege of distance education can be found in the sport a high dropout rate of undergraduate courses. By representing economic loss, not only to educational institutions, and for the country, reducing the chances of students in the fight for better market placements. For these reasons the study on this topic has grown in Brazil. In this paper we shall give birth to the sample data of students of Directors, in the distance, the Federal University of Maranhão, identify the factors that facilitated the evasion of the students in the course. The aforementioned study was conducted based on data in the Virtual Learning Environment - VLE students who dropped the course, and that, when the theoretical literature on the EAD was formulated, taking into account the issues of dialogue, structure and communication verification of coincidences collected by questionnaire responses and the themes of the theoretical Otto Peters, Michael Moore and Randy Garrison. Note that due to the expansion of offers of places in higher education institutions for distance education, this work is of major importance for the balance of pedagogical actions and administrative actions that envisage effective in practice to combat evasion courses higher in the distance.